An Ecofeminist Approach to Understanding Deficiencies in the Mining Regulatory Framework in South Africa - Malindi, Zanele (University of the Witwatersrand, Johannesburg, 2024)
Black women in rural areas of South Africa experience the harm in mining-affected communities more than other groups. This research report examines the legislative causes of this unequal distribution of harm. This report undertakes an analysis of the regulatory framework governing mining using the storytelling of two black, eco-activists in South Africa as the research methodology and ecofeminism as the theoretical premise to analyse and critique this framework. The issues of exclusion, limited participation, self-determination, violence, land rights, and legislative challenges are elucidated through the compelling stories of these two women and their legal battles in the pursuit of justice. Introducing ecofeminism as a theoretical framework, the paper underscores the shared oppression experienced by women and nature within patriarchal societies, advocating for the integration of ecofeminist principles into decision- making and legislative processes. In its conclusion, the paper calls for legislative reform, exposing the disparities between existing frameworks and the harsh realities faced by women, especially in environmental activism. Accentuating the pivotal role of women’s active participation and public engagement, it proposes these as essential steps towards a more equitable and sustainable future. The convergence of ecofeminist principles, inclusive decision-making, and public participation is presented not only as a moral imperative but also as a pragmatic necessity for addressing the intricate challenges posed by environmental degradation and gender-based discrimination.
A research report submitted in fulfillment of the requirements for the Master of Laws, In the Faculty of Faculty of Commerce, Law and Management, School of Law, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Ecofeminism; feminism; mining; mining law; eco-activism; environmental law; storytelling; MPRDA; IPILRA; TLGFA; TKLA; Balen; SDG-13: Climate action